Royalty Management Regulation for Song and/or Music Copyright: The Needs of Indonesian Musicians - Rokan, Mustika Putra (Locus: Jurnal Konsep Ilmu Hukum, 2021)
Problems often arise, namely related to the scope of legal protection to the Creator for his creation. This is something that most members of the public do not understand, especially song and/or music users. Many song users do not realize that what they are doing is a violation of Copyright, both for their economic rights or the moral rights of the Creators. On March 30, 2021, President Joko Widodo finally stipulates Government Regulation (PP) Number 56 of 2021 concerning Management of Song and/or Music Copyright Royalties, which is the mandate of Article 35 paragraph (3) of Law Number 28 of 2014 concerning Copyright. Apart from the problem of delays, the issuance of this PP on the Management of Song and Music Royalties has brought a breath of fresh air to songwriters in Indonesia. This is because the legal basis for collecting and distributing royalties is now stronger. Keywords: Copyright, Music, Royalties, Songs. Abstract Permasalahan sering muncul yaitu terkait ruang lingkup perlindungan hukum kepada Pencipta atas ciptaannya. Hal inilah yang belum bisa dimengerti oleh kebanyakan anggota masyarakat, terutama para pengguna lagu dan/atau musik. Banyak pengguna lagu yang tidak menyadari, bahwa apa yang dilakukannya merupakan sebuah pelanggaran terhadap Hak Cipta, baik atas hak ekonominya ataupun hak moral dari para Pencipta. Pada 30 Maret 2021, akhirnya Presiden Joko Widodo menetapkan Peraturan Pemerintah (PP) Nomor 56 Tahun 2021 tentang Pengelolaan Royalti Hak Cipta Lagu dan/atau Musik yang merupakan amanat Pasal 35 ayat (3) dari UU Nomor 28 Tahun 2014 tentang Hak Cipta. Di luar masalah keterlambatan, terbitnya PP Pengelolaan Royalti Lagu dan Musik ini membawa angin segar bagi para pencipta lagu di Indonesia. Sebab, kini dasar hukum pemungutan dan pembagian royalti jadi lebih kuat. Kata Kunci : Hak Cipta, Lagu, Musik, Royalti.